Wooden cantilevered staircase - Ghosh, Ayan (Jio Institute, 2023)
CSMT and the BMC building were among the first in Mumbai to use cantilevered staircases. The stairs were instead embedded in the wall at one end, with the other end 'free'. Sitaram Khanderao, who assisted Stevens on the BMC building, would go on to use cantilevered stairs for the Taj Mahal Palace Hotel, which he designed in collaboration with D.N. Mirza.